Project Managers' Competences in Managing Project Closing. Issue 3 (June 2019) - Wen, Qi; Qiang, Maoshan
Closing is a strategic but frequently overlooked project phase, in which project managers play pivotal roles as project team leaders. This study pinpoints project managers' competences underpinning the effective management of project closing, defined as project managers' closing competence (PMCC). A conceptual model of how PMCC contributes to project closing performance (PCP) was developed from related literature. Based on questionnaire data from 163 project management practitioners, partial least squares structural equation modeling (PLS-SEM) was employed to test the model and identify the most influential PMCC dimensions and indicators. The results reveal four PMCC dimensions (i.e., knowledge and skills, external stakeholder management, leadership in project team, and organization-level ability) significantly affecting PCP. The PLS-SEM results also quantify the relative importance of the indicators in each PMCC dimension. Comparing the findings with recent literature, we found that risk awareness, closing contract relationships, helping staff with career planning, participating in project closing decisions, and obtaining support from other departments are crucial aspects of PMCC that deserve more attention in research and practice. The findings heed the call for identifying competences according to project tasks, and operationalize PMCC and PCP into detailed indicators. The proposed PMCC framework also provides practical implications for project manager evaluation and selection.